Sosialisasi Tindakan Pertolongan Pertama Pada Kasus Cedera Olahraga (Sport Medicine) Para Pemain Sepak Bola di Desa Kubutambahan - MADE MARTINI pasek; Gede Budi Widiarta; G.Nur Widya Putra (PT FORMOSA CENDEKIA GLOBAL, 2022)
Injuries can occur due to physical stress, technical errors, excessive physical activity, or direct impact. The cause of injury can be divided into two factors, namely internal and external factors. Soccer players are prone to sports injuries, but in reality, some soccer players do not understand the initial management of a sports injury occurs so it is necessary to conduct socialization related to the initial management of sports injuries, the purpose of the activity is to increase understanding related to sports injury first aid, with socialization methods in the form of counselling and simulation for soccer players. The results of community service activities can increase the knowledge of soccer players and can take actions related to sports injury first aid.